The Munich Institute for the Study of the USSR origin and social composition - O'Connell, Charles T. (Univ. of Pittsburgh Center for Russian and East European Studies, 1990)
An examination of a research institute in Munich which the author claims was secretly funded by the CIA between 1951 and 1972 and used as a front for promulgating anti-Soviet propaganda.
Keywords: Munich Institute for the Study of the USSR -- Biography; Munich Institute for the Study of the USSR -- History; United States. -- Central Intelligence Agency -- Influence; Institut zur Erforschung der UdSSR; Geschichte; Deutschland; Sowjetunion; Soviet Union -- Research -- Germany -- Munich; Biografie